Changing gendered moral rationalities among Israeli welfare-to-work participants. Issue 1 (1st January 2020) - Herbst-Debby, Anat; Benjamin, Orly
ABSTRACT: European and North American feminist economists have challenged the assumption that job remunerations can cover single mothers' breadwinning needs. Notwithstanding the strength of this argument, a less economic argument against welfare-to-work (WTW) policy is that it fails to consider women's community-anchored gendered moral rationalities (GMRs). What previous studies rarely grasped is the opportunity provided by WTW to theorize the conditions under which the ability to negotiate cultural values and beliefs held by communities modify the understanding of opportunities. GMRs, which combine the economic with the cultural, were defined as embedded within communities' and families' cultural values, which in their turn, condition the extent to which extended families support mothers. The current study examines stable and changing GMRs of single mothers from diverse ethno-national communities. Our analysis of the interviews of 62 mothers who participated in a specific WTW program in Israel and shouldered the expectation to enter the labor market reveals that, when a program is based on a supportive women's group and provides occupational training opportunities, GMRs can change so that women negotiate their communities traditional constructions of motherhood.